2019
DOI: 10.1093/cid/ciz431
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intussusception After Oral Monovalent Rotavirus Vaccination in South Africa

Abstract: Background Postlicensure studies have shown an association between rotavirus vaccination and intussusception. We assessed the risk of intussusception associated with Rotarix (RV1) administration, at 6 and 14 weeks of age, in an upper-middle-income country, South Africa. Methods Active prospective surveillance for intussusception was conducted in 8 hospitals from September 2013 through December 2017. Retrospective case enrollm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 26 publications
7
27
1
Order By: Relevance
“…In this study no case was observed before 6 weeks, one case before 10 weeks and 11 cases before 14 weeks of ages. This observation is similar to that from African countries [23] , [28] . The median or peak ages of intussusception in children from the countries with increased risk were also comparable to the Indian and African children.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study no case was observed before 6 weeks, one case before 10 weeks and 11 cases before 14 weeks of ages. This observation is similar to that from African countries [23] , [28] . The median or peak ages of intussusception in children from the countries with increased risk were also comparable to the Indian and African children.…”
Section: Discussionsupporting
confidence: 89%
“…Our results are comparable to the reports of intussusception after RV1 (Rotarix™) vaccination in several African countries (Ethiopia, Ghana, Kenya, Malawi, Tanzania, Zambia, Zimbabwe and South Africa), where no increased risk of intussusception after any dose of RV1 were observed [23] , [28] . However, increased risks of intussusception were documented in the 1–7 days following dose 2 of RV1 in Brazil (IR 2.6; 95% CI 1.3–5.2; OR 1.9; 95% CI 1.1–3.4) and after dose 2 (IR 5.3; 95% CI 3.0–9.3 and OR 5.8; 95% CI 2.6–13) and dose 1 (IR 6.49; 95% CI 4.17–10.09) in Mexico [9] , [10] .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Despite the hypothesis that intussusception might be an adverse event associated with all rotavirus vaccines 11 , the World Health Organization (WHO) recommended rotavirus vaccine introduction into childhood vaccination programs as cases and deaths averted due to diarrhea are greater than the additional intussusception, resulting in a favourable risk benefit analysis 12 . Recently, our understanding of the safety of rotavirus vaccination in specific populations was further informed by the finding that in seven low-income African countries and South Africa, where vaccine efficacy has been lower than that seen in high-income countries, there was no increased risk of intussusception following Rotarix® vaccination 13 , 14 .…”
mentioning
confidence: 99%
“…Some increased risk of intussusception after the first (relative risk, RR: 4.7–13.8) and second (RR: 1.3–5.3) doses of RVVs was reported from several countries (Mexico, Brazil, Australia, United Kingdom, United States, Spain and Singapore) [ 1 8 ]. But no increased risk of intussusception after any dose of RVV was observed in some countries (Ethiopia, Ghana, Kenya, Malawi, Tanzania, Zambia, Zimbabwe and South Africa) [ 9 , 10 ]. The impact of RVV on diarrhoea morbidity and mortality outweigh the risk of intussusception and associated mortality [ 11 ].…”
Section: Introductionmentioning
confidence: 99%